The Effects of Language and Semantic Repetition on the Enactment Effect of Action Memory - Zhang, Xinyuan; Zuber, Sascha (Frontiers in Psychology, 2020)
Humans exhibit enhanced memory performance when information is encoded by physically performing it, as opposed to passively reading or listening to the phrases; an effect referred to as “enactment effect”. The present study explored the effects of language form (native vs. non-native) and semantic level (repeated vs. non-repeated) on enactment effect in action memory. Forty-eight subjects were required to learn action phrases either by enacting or by reading the items. The results showed i) a better memory performance for enacted phrases ii) enhanced memory performance for action phrases in the non-native language learning, and iii) a memory benefit due to semantic level (deep processing) for non-native language but under passive encoding. The findings are discussed within the light of the multimodal theory.